Chemistry in confined space through the eyes of surface science—2D porous materials. (21st December 2018) - Boscoboinik, J Anibal
Abstract: There are a rapidly growing number of studies showing exciting new opportunities in the way confinement effects on surfaces affect the properties of materials and their chemistry. These effects have been observed recently under two-dimensional (2D) van der Waals materials such as a graphene and boron nitride and for the case of supported 2D-porous oxides, including silicates, aluminosilicates and zeolite nanosheets. This review summarizes the current state of the art in this area of research and how confinement effects in 2D systems relate to those found in 3D porous and layered materials. The focus of this review is put in 2D-materials with inherent porosity, such as 2D-porous oxides. An outlook is also given for the future of this exciting emerging area.